Physiologic left ventricular cavity dilatation in elite athletes - Pelliccia, A.; Culasso, F.; Di Paolo, F. M.; Maron, B. J. (Annals of Internal Medicine, 1999)
BACKGROUND: Absolute left ventricular cavity dimension may be substantially increased in some highly trained athletes. This raises questions about the differential diagnosis between athlete's heart and dilated cardiomyopathy as well as possible disqualification from competitive sports. OBJECTIVE: To evaluate the morphologic characteristics and physiologic limits of left ventricular cavity enlargement associated with intensive, long-term athletic conditioning. DESIGN: Evaluation of left ventricular cavity dimension in a large sample of highly trained athletes. SETTING: Institute of Sports Science, Rome, Italy. PARTICIPANTS: 1309 elite Italian athletes (957 men and 352 women), 13 to 59 years of age (mean, 24 years), participating in 38 different sports. MEASUREMENTS: Echocardiographic assessment of left ventricular cavity dimension and multivariate statistical analysis of the determinants. RESULTS: Left ventricular end-diastolic cavity dimensions varied widely (38 to 66 mm [mean, 48 mm] in women and 43 to 70 mm [mean, 55 mm] in men) and was within generally accepted normal limits for most participants (< or = 54 mm in 725 athletes [55%]). According to an arbitrary clinical cut-point of 60 mm, the left ventricular cavity was substantially enlarged in 185 participants (14%). These athletes had global left ventricular systolic function within normal limits and no regional wall-motion abnormalities; participants remained free of cardiac symptoms and impaired performance over 1 to 12 years (mean, 4.7 years). The major determinants of cavity dimension were greater body surface area and participation in certain endurance sports (cycling, cross-country skiing, and canoeing). CONCLUSIONS: In a sample of highly trained athletes, left ventricular cavity dimension varied widely but was strikingly increased to a degree compatible with primary dilated cardiomyopathy in almost 15% of participants. In the absence of systolic dysfunction, this cavity dilatation is most likely an extreme physiologic adaptation to intensive athletic conditioning. The long-term consequences and significance of this marked left ventricular remodeling of the athlete's heart is not known.